Factors Driving Contemporary Islamic Civilization From Iran's Shiah Perspective - Kusumo, Aditya Aryo Nur (Journal of Islamic Civilization, 2023)
During Mohammad Reza Shah Pahlavi’s regime, around 250,000 shops were closed, 31,000 traders were imprisoned, and many clerics and civilians were killed. Additionally, 70% of the newspapers in Iran were shut down. However, in 1979, the Iranian revolution took place, led by Imam Ayatullah Khomeini. This revolution was a turning point for Iran as it aimed to restore the glory of Islamic civilization in Iran. The Iranians believe that Islamic civilization is the best civilization and can bring justice. This paper aims to discuss the efforts made by Iranian Shiites in restoring the glory of Islamic Civilization from various perspectives such as religious, cultural, educational, and psychological. The research method used for this paper is qualitative, involving library research with data collection techniques through literature study and content analysis of research journals related to Iranian Shia civilization. After the Iranian revolution, Iranian Shiites reconstructed religious thought and cultural engineering. They also implemented the Imamiyah education system as the primary driving force. Moreover, the Iranian Shiite community can achieve their lofty ideals with good psychological aspects.